The role of ultrasonography in acute appendicitis - Lamture, Yashwant R.; Gajbhiye, Varsha P.; Shahapurkar, Vinay V. (International Surgery Journal, 2017)
Background:Acute appendicitis is the most common surgical emergency. Inspite of new investigations, mainstay of diagnosis depends on clinical sign and symptoms, laboratory and USG (ultrasonography) of abdomen. Out all these investigations USG is having a crucial role in a diagnosis of it. Hence this study was undertaken to prove its efficacy. Methods: This study was conducted in 418 patients with 186 females and 251 males. Patients were of acute appendicitis operated for appendicectomy were included in the study. Data analysis was done by Stata statistic software. Before surgery patients were subjected for necessary investigations including USG. Results:The mean age was 18.8 (range 8-83) years. Normal appendix found in 22 cases, hence negative appendicectomy rate was 6.6%. Chronic appendicitis was found in 28 patients. Different pathology was found in 1 in the form of carcinoid of appendix (0.24%) but treated by appendicectomy. USG abdomen in present study showed sensitivity of 88.6% and specificity 92% with PPV and NPV was 98% and 52.3%, frequency reports were s/o acute appendicitis in 337 patients and normal in 82 subjects. Conclusions:It conclude that USG is very important tool to diagnose and rule out appendicitis and its complications like perforation or peritonitis. Its liberal use by expert radiologist can help to reduce negative appendicectomy rate.